An adaptive governance and health system response for the COVID-19 emergency - Khan, Mushtaq; Roy, Pallavi; Matin, Imran; Rabbani, Mehnaz; Chowdhury, Rajiv (Science Direct, 2022)
This article was published in World Development [©2020 Published by Elsevier Ltd. All rights reserved.] and the definite version is available at: https://doi.org/10.1016/j.worlddev.2020.105213 The Article's website is at: https://www.sciencedirect.com/science/article/pii/S0305750X20303405